ANALYSIS OF TAX JUSTICE AND COMPLIANCE COSTS AND TAX RATES AGAINST TAX EVASION ACTIONS IN SAMARINDA - Jannah, Putri Raudatul; Iskandar, Iskandar (Univesitas Muhammadiyah Tangerang, 2025)
Tax evasion is the act of breaking the law by hiding or falsifying financial information in order to avoid paying taxes that should be paid. Filling out an incorrect income tax return is a form of tax evasion because it is a violation of the law. The government's lack of firmness in responding to fraudulent tax payments, taxpayers' lack of knowledge about their rights and responsibilities in paying taxes, and tax rates that are too high, all contribute to taxpayers' ability to engage in tax evasion. This research aims to determine and analyze tax fairness, compliance costs, and tax rates for acts of tax evasion registered at KPP Pratama Samarinda Ulu. This type of research is quantitative using primary data, namely a questionnaire with 29 statements. The sampling method used was purposive sampling and the total sample size was 269 individual taxpayer respondents, certain entrepreneurs registered at KPP Pratama Samarinda Ulu. This research uses data analysis tools carried out with Partial Least Square (PLS) ver 3.0. The results of this research show that tax justice has a negative and significant effect on acts of tax evasion, compliance costs have a negative and significant effect on acts of tax evasion, and tax rates have a negative and significant effect on acts of tax evasion.